DETECTION OF DEEP VEIN THROMBOSIS BY 99mTc-SULFUR COLLOID IN 24 CASES - RUKSAWIN, Nisarut; PHORNPHIBULAYA, Pramot (The ASEAN Journal of Radiology, 2023)
Scintigrams of the legs were recorded by computed scinticamera after antecubital injection of 99mTc-sulfur colloid in 24 patients with suspected deep vein thrombosis. Contrast venogram were taken after the scan 1 hour to 1 day. Of 15 patients with confirmed deep venous thrombosis, 11 had positive scans. Of 9 patients with normal venograms, 8 had negative scintigrams. Rate of accuracy read by physician was 79% and rate of accuracy analysed by computer was 83%. The risk and discomfort of contrast studies may be eliminated by the nuclear method.